Ritual Village Music And Marginalised Musicians Of Western Orissa/odisha, India - Guzy, Lidia (Penerbit Universiti Sains Malaysia (USM Press), 2013)
This work presents the summarised results of an anthropological and ethno-musicological documentation of hitherto unknown traditions of sacred music performed by marginalised musicians and priest-musicians of the Adivasi (indigenous) Bora Sambar region of western Orissa/Odisha, India. The work is based on more than 30 months of ethnographic research in rural regions of western Orissa/Odisha.